Role of the Internet in Spreading Rumors Social networking sites "Facebook" model For the duration of 1-7-2017 until 30-11-2017: يوسف محمد حسين (Al-Academy, 2019)
This study is about the role of the Internet in spreading rumors, especially through social networking sites "Facebook" model as the effectiveness of social networks lies in the speed of transmission of events; these two characteristics are important to the public, making the Internet a strong contender for television and its relationship with the public. That's why we find that the Internet today has become a fertile environment for the growth and spread of rumors. The more limited the platforms and places of publication, the greater the responsibility in the search for the original source in spreading this or that rumor, as the Internet is considered an easy means in the production, spreading and re-spreading of information and sharing updates on events by the easiest and least costing methods and in short periods of time, as well the ability to control the electronic content is very small, in addition to the difficulty of monitoring the content published by others.Today, Facebook has become one of the most important means of spreading rumors of all kinds in society, i.e., political, economic and social